2020
DOI: 10.3390/ijerph17197042
|View full text |Cite
|
Sign up to set email alerts
|

Care Dependency in Patients with Heart Failure: A Cross-Sectional Study in Spain

Abstract: Background: Heart failure (HF) is a progressive and debilitating condition that represents an ever-growing problem for health systems worldwide. HF patients feel that they are a burden on their families, they feel socially isolated and have a low perception of their health. Accordingly, the objectives of this study were to: (1) to explore the profile of care dependency in a representative sample of Spanish HF patients through the Care Dependency Scale (CDS), and (2) to identify correlates of care dependency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In this study, patients who scored >44 were treated as highly care‐independent, and those who scored ≤44 were treated as highly care‐dependent. This scale has been validated in different populations and is found to be easy to use and quick to complete (Juárez‐Vela et al, 2020). This scale also has shown good construct validity in the Chinese population which established by Zhang et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, patients who scored >44 were treated as highly care‐independent, and those who scored ≤44 were treated as highly care‐dependent. This scale has been validated in different populations and is found to be easy to use and quick to complete (Juárez‐Vela et al, 2020). This scale also has shown good construct validity in the Chinese population which established by Zhang et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…The men belonging to a younger examined age group (average age of 77.46 ± 9.76 years) reported lower care dependency than those who belonged to the older group (average age of 83.05 ± 7.20 years). Moreover, the study proved that care dependency in men increases with their age [ 13 ]. An increase in care dependency, along with age, measured by means of the CDS was also observed in a study conducted by Lohrmann et al on a group of 1806 patients aged over 60 and hospitalized in various German hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The internal consistency of this scale was confirmed by a high Cronbach’s alpha coefficient (0.98). Previous studies also showed that the Polish version of the CDS can be used to compare and develop international standards of assessment as far as older patients’ needs are concerned [ 6 , 8 , 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation